2015
DOI: 10.1002/2015ja021005
|View full text |Cite
|
Sign up to set email alerts
|

MHD simulations using average solar wind conditions for substorms observed under northward IMF conditions

Abstract: Substorms are known to sometimes occur even under northward interplanetary magnetic field (IMF) conditions. In this paper, we perform three‐dimensional global magnetohydrodynamic simulations to examine dayside reconnection, tail, and ionospheric signatures for two cases of substorm observations under prolonged northward and dawnward IMF conditions: (1) a strongly northward/dawnward IMF case with BIMF = (0, −20, 20) nT; (2) a weakly northward/dawnward IMF case with BIMF = (0, −2, 2) nT. Throughout the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Moving on to comparisons with other recent results, there are some similarities between the features of our simulation run and the results of Li et al (2021), but there are also some interesting differences. Initially, one might expect the closed wedge to contract and be associated with strong earthward flows, similar to those traditionally associated with northward IMF substorm conditions as discussed by Lee et al (2010), Miyashita et al (2011), Park et al (2015, Li et al (2021), and references therein. However, in our simulation, it is clear (from the middle panels in Figure 2) that the wedge increased in length toward more negative X-values rather than forming and contracting earthward.…”
Section: Discussionmentioning
confidence: 70%
“…Moving on to comparisons with other recent results, there are some similarities between the features of our simulation run and the results of Li et al (2021), but there are also some interesting differences. Initially, one might expect the closed wedge to contract and be associated with strong earthward flows, similar to those traditionally associated with northward IMF substorm conditions as discussed by Lee et al (2010), Miyashita et al (2011), Park et al (2015, Li et al (2021), and references therein. However, in our simulation, it is clear (from the middle panels in Figure 2) that the wedge increased in length toward more negative X-values rather than forming and contracting earthward.…”
Section: Discussionmentioning
confidence: 70%
“…Substorm, the main process of solar wind entry during southward IMF condition, was not supposed to occur during northward IMF condition. However, recent observations have shown that substorms did occur during northward IMF condition [ Du et al , ; Lee et al , ; Park et al , ; Peng et al , ; L. Q. Zhang et al , ; Park et al , ]. Such substorms may significantly facilitate solar wind entry in the magnetotail during northward IMF condition.…”
Section: Discussionmentioning
confidence: 99%
“…Now there are growing evidences that the tail X line also occurs for NW-IMF [e.g., Park et al, 2015;Zhang et al, 2015c]. According to Zhang et al [2015c], the near-Earth X lines occur for SW-IMF as well as NW-IMF, but more frequently for SW-IMF.…”
Section: Introductionmentioning
confidence: 99%